2017
DOI: 10.21817/ijet/2017/v9i4/170904119
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Welding by Friction Stir Welding of C3064 Brass with AA1100 Aluminum Alloy

Abstract: Abstract-This research aims study parameters in the dissimilar butt-joint of AA1100 aluminum alloy with C3604 brass by using a FSW process. The parameter is rotation speed 660, 1110 and 1320 rpm, travel speed at 80 and 160 mm/min, lead angle 3 degree and pin tool cylindrical shape from JIS-SKH 57 carbon steel. The experimental results show that FSW between both materials bonded together very well. The increase of rotation speed with lower travel speed is likely to increase the tensile strength as well. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…It was found that the SZ had a higher hardness than that of the base metal (BM) caused by the effects of friction force that also caused Al2Cu phase to be broken and dispersed around the SZ. Moreover, the heat was another cause that affected the structural changes of the SZ until it led to increased hardness [13]. The intermetallic compound was formed by heat, and the transition of the eutectic phase in various forms would promote good hardness.…”
Section: Vickers Hardness Resultsmentioning
confidence: 99%
“…It was found that the SZ had a higher hardness than that of the base metal (BM) caused by the effects of friction force that also caused Al2Cu phase to be broken and dispersed around the SZ. Moreover, the heat was another cause that affected the structural changes of the SZ until it led to increased hardness [13]. The intermetallic compound was formed by heat, and the transition of the eutectic phase in various forms would promote good hardness.…”
Section: Vickers Hardness Resultsmentioning
confidence: 99%